Penatalaksanaan Anemia Ringan dengan Pemberian Buah Pepaya di Puskesmas Way Kandis Tahun 2023 - Wahyuni, Iin; Salsabila, Amalya Shofa; Destri, Yuhelva; Sutrinigsih, Sutrinigsih (Penerbit Goodwood, 2024)
Purpose: The student is able to provide midwifery care for pregnant women with the management of mild anemia in Mrs. E, aged 34, G3P2A0, at 30 weeks and 6 days of pregnancy, focusing on the administration of papaya fruit at the Way Kandis Health Center, Bandar Lampung, in 2023. Method: The type of report used is a case report with a descriptive approach through a case study (case review study). A case study was conducted by investigating an issue using a case consisting of a single unit. Results: Midwifery care was carried out to collect baseline data on the condition of the patient, Mrs. E, aged 34 years, G3P2A0, at 30 weeks and 6 days of pregnancy, with the management of mild anemia focusing on the administration of 110 g of papaya per day at the Way Kandis Health Center, Bandar Lampung. Limitations: The study focused on a single case, specifically Mrs. E, which limits the generalizability of the results to a wider population. Contributions: This article highlights a practical, natural remedy, papaya fruit, for the management of mild anemia in pregnant women, providing a low-cost and easily accessible intervention.